New Hope for the Oceans: Engaging Faith-Based Communities in Marine Conservation - Schaefer, Jame (Frontiers in Marine Science, 2017)
Science alone cannot mitigate threats to the oceans. Whereas scientists can identify problems and empirical steps toward their resolution, support for research, problem solving, and implementation of solutions must come from societal sources. Among the most promising are religious communities whose members are motivated by their faith to collaborate with marine scientists in achieving shared goals. Many reasons prevail for engaging faith communities in mitigating assaults on the oceans and protecting them from threats to their functioning. Participants in the open forum convened by the Religion and Conservation Biology Working Group of the Society for Conservation Biology during the 4th International Marine Conservation Congress shared their insights on (1) why and how marine researchers and conservation practitioners can best involve faith communities, (2) actions and attitudes that deter constructive engagement with faith communities, and (3) ways forward that the SCB should consider facilitating. Among ways forward identified are the Best Practices Project initiated recently by the RCBWG, adding cultural values and ethics as disciplines SCB members should probe when addressing conservation problems, regularly including cultural values and ethics in panels with other disciplines at international and regional SCB congresses, and appointing an associate editor of SCB publications who will assure the inclusion of articles in which religious and spiritual worldviews, values, and ethics are integrated with the conservation sciences.